Flexible CdS and PbS nanoparticles sensitized TiO2 nanotube arrays lead to significantly enhanced photocatalytic performance. Issue 18 (15th December 2020) - Hou, Junwei; Yang, Ye; Zhou, Jingyi; Wang, Yafei; Xu, Tengze; Wang, Qingyao
Abstract: TiO2 nanotube arrays (TiO2 NTAs) were mainly synthesized by the anodization of Ti foils, and the Ti mesh anodization was little researched. TiO2 NTAs/Ti mesh showed remarkably high photocatalytic performance in pollutant treatment and photocurrent/hydrogen generation. In this paper, TiO2 NTAs were synthesized on flexible three dimensional Ti mesh surface, and CdS/PbS sensitizers covered TiO2 NTAs by the hydrothermal deposition. Especially, the S –CdS photocatalyst prepared by CdS sensitization showed strong photocurrent and photocatalytic pollutant removal capacity. RhB, MB dyes and Cr(VI) ions were effectively purified under solar irradiation, and samples also showed excellent visible light-driven photoelectric ability. Furthermore, the S –PbS photocatalyst prepared by PbS sensitization showed high photocatalytic water splitting performance. The functional material offers a flexible, low cost and high photocatalytic membrane for waste water treatment and photocurrent/hydrogen generation.